Persepsi Masyarakat Terhadap Bencana (Mass Perception Of Disaster) - Ahmad Sabir (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2018)
This study intends to analyze public perception of the disaster. The purpose of this study is specifically intended to answer research questions about how people's perceptions of the disaster in Indonesia, both from the perspective of those affected by the disaster, as well as from people who are not or have not been affected by the disaster. This study used a qualitative method with phenomenological approach and psychological anthropology. The process of data collection is done through a method of documentation library, free interviews and interpretation of diverse views within the community perspective on the reality of the disaster in Indonesia. A preliminary interpretation fatalist tendency in society perspective of looking at natural disasters of Mount Merapi. Followed by escapism for the disaster that the shape can be jumped into a religious faith or inclination to memitologisasi disaster. In addition, there is a different interpretation in the perspective of those who are not or have not been affected by the disaster, especially those who do not are planted in the disaster, which saw the disaster as a profitable commodity, whether it is regarded as a political commodity as well as the capitalization of the disaster.